Incipient gallbladder carcinoma. Clinical and pathological study and prognosis in 196 cases - Roa, I; de Aretxabala, X; Araya, J C; Villaseca, M; Roa, J; Guzmán, P (Revista medíca de Chile, 2001)
There is little information about the behavior of early gallbladder carcinoma. To report the clinical and pathological features of 196 patients with early gallbladder carcinoma. All patients with gallbladder cancer diagnosed between 1988 and 1997 were reviewed. In 703 of 829 patients, there was information about clinical features and follow up, and were included in this study. All gallbladders were subjected to a complete mapping. When neoplastic cells involved only the mucosa or muscular layer, the tumors were considered as early. One hundred ninety six patients had an early carcinoma (161 women, aged 57.5 years and 35 male, aged 63.4 years). One hundred twenty eight tumors were located in the mucosa and 68 in the muscular layer. Patients with tumors involving the mucosa were younger than those with tumors involving the muscular layer. All tumors were adenocarcinomas, 66% were well differentiated and 32% moderately differentiated. Tumors were not visible macroscopically in 132 cases. Five and 10 years survival was 92%. Subjects of less than 40 years old had a 100% survival at 5 years. A hepatic and lymph node resection was done in 12 patients with tumors infiltrating the muscular layer but in only one, the tumor infiltrated the liver. No difference in survival was observed when a simple cholecystectomy or radical surgery was done. Nearly 25% of gallbladder carcinomas can be classified as early and its diagnosis requires a directed study. Simple cholecystectomy is curative for this type of gallbladder cancer.